Association of blood inflammatory phenotypes and asthma burden in children with moderate-to-severe asthma - Amir Hossein Alizadeh Bahmani; Susanne J.H. Vijverberg; Simone Hashimoto; Christine Wolff; Catarina Almqvist; Lizan D. Bloemsma; Susanne Brandstetter; Paula Corcuera-Elosegui; Mario Gorenjak; Susanne Harner; Anna M. Hedman; Michael Kabesch; et al. (ERJ Open Research)
Background Underlying immunological mechanisms in children with moderate-to-severe asthma are complex and unclear. We aimed to investigate the association between blood inflammatory parameters and asthma burden in children with moderate-to-severe asthma. Methods Blood inflammatory parameters (eosinophil and neutrophil counts and inflammatory mediators using multiplex immunoassay technology) were measured in children (6–17 years) with moderate-to-severe asthma from the SysPharmPediA cohort across four European countries. Based upon low/high blood eosinophil (LBE/HBE) counts of </≥0.3×109·L−1, respectively and low/high blood neutrophil (LBN/HBN) counts of </≥4×109·L−1, respectively, mixed (HBE-HBN), eosinophilic (HBE-LBN), neutrophilic (LBE-HBN) and paucigranulocytic (LBE-LBN) phenotypes were defined. Inflammatory mediator profiles and burden of disease (asthma control status, exacerbations and school days missed in the past year) were compared between phenotypes using adjusted logistic regression models. Results Among 126 included children (41% girls and mean (sd) age of 11.94 (2.76)), 22%, 44%, 11% and 23% were classified as mixed, eosinophilic, neutrophilic and paucigranulocytic phenotypes, respectively. Neutrophilic children had the lowest lung function (forced expiratory volume in 1 s % predicted pre-salbutamol) compared with other groups. Children with mixed asthma were most often uncontrolled and had the highest asthma-related school absence in the past year. Interleukin (IL)-6 and matrix metalloproteinase-9 levels were significantly higher in patients with mixed or neutrophilic asthma, whereas tissue inhibitor of metalloproteinase-2 was lower in patients with neutrophilic asthma compared with eosinophilic or paucigranulocytic asthma. IL-5 was increased in eosinophilic group compared with the neutrophilic and paucigranulocytic groups, irrespective of the chosen cut-off for eosinophilia. Conclusion Differences in asthma burden-related clinical expression and distinct blood inflammatory mediator profiles were found between phenotypes, highlighting implications for optimising personalised treatment and management strategies in children with moderate-to-severe asthma.